1985
DOI: 10.2337/diab.34.2.s1
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus: Heterogeneity of Maternal Age, Weight, Insulin Secretion, HLA Antigens, and Islet Cell Antibodies and the Impact of Maternal Metabolism on Pancreatic B-Cell and Somatic Development in the Offspring

Abstract: We have examined gravida with gestational diabetes mellitus (GDM), as defined by the National Diabetes Data Group (Diabetes 1979; 28:1039), for phenotypic and genotypic heterogeneity. Fasting plasma glucose (FPG) at diagnosis was used for further stratification of GDM according to putative metabolic severity into class A1 (FPG less than 105 mg/dl [N = 129]), class A2 (FPG 105-129 mg/dl [N = 47]), and class B1 (FPG greater than or equal to 130 mg/dl [N = 23]). All GDM classes tended to be older and heavier than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
3
4

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(75 citation statements)
references
References 0 publications
3
65
3
4
Order By: Relevance
“…This may, however, represent an over correction, as the HLA genotypes tested are in strong linkage disequilibrium [45] and thereby do not represent independent observations. A report showed a two-fold increase in the frequency of HLA-DR3 and -DR4 antigens in GDM compared with the controls matched for race, and the increase was statistically significant in black women from the Unit- ed States [22]. Another study found no significant difference in the frequency distribution of HLA-DQB1, -DQA1 and -DRB1 alleles between Caucasian GDM and control women from Germany [46].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This may, however, represent an over correction, as the HLA genotypes tested are in strong linkage disequilibrium [45] and thereby do not represent independent observations. A report showed a two-fold increase in the frequency of HLA-DR3 and -DR4 antigens in GDM compared with the controls matched for race, and the increase was statistically significant in black women from the Unit- ed States [22]. Another study found no significant difference in the frequency distribution of HLA-DQB1, -DQA1 and -DRB1 alleles between Caucasian GDM and control women from Germany [46].…”
Section: Discussionmentioning
confidence: 91%
“…Increased frequencies of HLA-risk antigens and high prevalence of ICA, insulinoma-associated antigen 2 (IA-2) and GAD antibodies have also been reported in women with GDM [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…HLA genes of the MHC have been related to GDM in several studies. Some have demonstrated a positive association between GDM and HLA class II alleles [2], while others have not [3]. If GDM is to be properly classified, it is necessary to genetically characterise it and make distinctions from other types of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…3 Khan et al in his study concluded that maternal age, BMI, previous history of gestational diabetes and family history of diabetes are the high-risk factors of GDM. 4 This association of increasing age with GDM might be due to the declining beta cell function and insulin sensitivity.…”
Section: Figure 1: Comparison Of Mean Values Of Interleukin-6mentioning
confidence: 99%